Recovery of Reactive (Triazine) Dyes from Textile Effluent by Solvent Extraction Process - TUTEJA*, RAVINDER; KAUSHIK, NAMRATA; KAUSHIK, C.P.; SHARMA, J.K. (Asian Journal of Chemistry, 2024)
In the present work, triazine reactive dyes are recovered from thetextile effluent by the solvent extraction process using surfactants. Workis carried out on three different triazine dyes i.e., reactive blue 171,reactive red 141 and reactive yellow 84. As these dyes are anionic innature so cationic surfactant i.e., hexadecyl trimethyl ammonium bromide(HTAB) is used for the forward extraction of dye into solvent phase.For the backward extraction of dye into aqueous phase an anionicsurfactant is used to counter the charge effect i.e., sodium dodecylbenzene sulfonate (SDBS). The cationic surfactant is chosen in such away that it forms reverse micelle with solvent. Isoamyl alcohol is selectedas solvent for the present studies, since the other lower alcohols aresoluble in water, where as it is almost immiscible and forms distinctupper layer in aqueous solution. The effects of different parameters,such as the surfactant concentration, pH and electrolyte (NaCl) concentrationare studied in the present work.